Kajian Interaksi Obat Pada Pasien Demam Tifoid di Rumah Sakit X di Surakarta - Eersta Zusvita Widyastuti; Adhi Wardhana Amrullah; Agnes Prawistya Sari; Avianti Eka Dewi Aditya Purwaningsih (Jurnal Farmasi Indonesia, 2024)
Salmonella typhi bacteria reside in the human body and cause an infection known as typhoid fever. The number of cases of typhoid fever in Indonesia reaches 81% per 100,000 people. The use of various drugs in the treatment of typhoid fever will increase the possibility of drug interactions. This research is a descriptive observational cross-sectional study. Data from medical records of typhoid fever patients at "X" Hospital in Surakarta from January to December 2021 were used in this study. Potential drug interactions were analyzed using the Drug Interaction Checker application and Stockley's Drug Interaction Guidebook. The data were then statistically analyzed using SPSS 25. The results showed that out of 96 patients with typhoid fever, 29 experienced potential drug interactions. Of the 29 patients, 68 cases occurred, consisting of 41 non-antibiotic-non-antibiotic cases (60.3%) and 27 antibiotic-non-antibiotic cases (39.7%). The highest potential drug interactions were levofloxacin and ondasetron in 8 cases, dexamethasone-omeprazole in 7 cases, ceftriaxone-lansoprazole in 5 cases and sucralfate-lansoprazole in 5 cases. Based on the level of severity, the potential drug interactions that are minor are 26 cases (38.235%), moderate drug interactions are 26 cases (38.235%) and major interactions are 16 cases (23.53%). Based on the mechanism, the most potential drug interactions in pharmacokinetics occurred, namely 52 cases (72.47%) compared to pharmacodynamics as many as 16 cases (23.53%).